Contemporary Arabic Literature as a Medium of Resistance and Social Transformation: A Qualitative Study of the Palestinian Issue and Arab Feminism - Saripa Balqis Alqadri; Haniah; Muhsin (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2026)
Contemporary Arabic literature has evolved into a medium that is not only aesthetically valuable, but also loaded with ideological, social, and political dimensions. This article aims to examine two of the most dominant global issues in contemporary Arabic literature, namely the Palestinian conflict and the Arab feminist movement. The research uses a qualitative-descriptive approach with the methods of literary criticism and literature review, as well as applying the conceptual framework of adab al-muqāwamah and postcolonial feminism. The results of the study show that Palestinian resistance literature functions as a documentation of collective memory, a tool for shaping political consciousness, and a space for psychological recovery. The works of Mahmoud Darwish and Ghassan Kanafani are the main representations of this tradition. Meanwhile, Arab feminist literature represented by Nawal El Saadawi and Hanan Al-Shaykh marks the transformation of women from objects of representation to subjects who voice their own life experiences. These two literary currents have a common point in the concept of intersectionality, which is a combination of the struggle for national liberation and gender equality. This study confirms that contemporary Arabic literature functions as a medium of resistance and social transformation that brings together the struggle for national liberation with the struggle for gender equality.